The depiction of marketing and marketers in the news media - Cluley, Robert (Emerald Group Publishing Limited, 2016)
Purpose – In an effort to explain the high level of scepticism and distrust towards marketing and marketers, paper explores how marketing practice and practitioners are depicted in the mass media. Design/methodology/approach – The paper analyses 6,877 news reports that discuss “marketing” across two one-year time periods from three UK newspapers. A systematic content analysis is presented through N-Grams and K-Grams, close readings of individual cases and manual coding. Findings – The paper finds that the news media cultivates an image of marketing and marketing practitioners whereby marketing is portrayed in the news as a cost to businesses and something that businesses do to consumers. The study finds that marketers are also presented through a narrow viewpoint. Marketers are depicted as male and tend to be viewed a source of authority only when speaking on behalf of their organizations in response problems and crises. Research limitations/implications – The cultivation effect of mass media is widely accepted among communications scholar, yet its use within marketing research is limited. The paper represents an empirical application of this approach. Practical implications – Organizations including the Chartered Institute of Marketing and American Marketing Association have attempted to counteract marketing’s image problem by redefining what marketing means. The results of this study suggest that such attempts are unlikely to work as the practice of marketing, in particular PR, cultivates a negative image in the media. Originality/value – The paper demonstrates the utility of cultivation theory and systematic content analyses of media texts. It develops a methodology to examine how professional practice is depicted in mass media.